The role of potential probiotic strains Lactobacillus reuteri in various intestinal diseases: New roles for an old player - Yu, Zihan; Chen, Jihua; Liu, Yaxin; Meng, Qingguo; Liu, Hang; Yao, Qinyan; Song, Wenxuan; Ren, Xiangfeng; Chen, Xin (Frontiers in Microbiology, 2023)
Lactobacillus reuteri is a gut symbiont which can be colonized in the intestine of human, also a type of Lactobacillus spp. Since first isolated in 1962, a multitude of researches have been conducted to investigate its role in different diseases particularly in intestinal diseases. While a growing body of studies focus on Lactobacillus reuteri, there are still lots of doubts concerning its curative effects and precise mechanisms. In this review, we initially interpreted the basic function of Lactobacillus reuteri and its related metabolites. Next, we comprehensively summarized its function in different intestinal diseases, containing inflammatory bowel disease, colorectal cancer, infection-associated bowel disease and pediatric intestinal disorders. We also highlighted some important molecules in relation to the underlying mechanisms. In conclusion, Lactobacillus reuteri has the potential to exert beneficial impact on intestinal diseases, which should be further explored so as to obtain better clinical application and therapeutic effects.